2020
DOI: 10.3390/ijms21186856
|View full text |Cite
|
Sign up to set email alerts
|

FGFR Fusions in Cancer: From Diagnostic Approaches to Therapeutic Intervention

Abstract: Fibroblast growth factor receptors (FGFRs) are tyrosine kinase receptors involved in many biological processes. Deregulated FGFR signaling plays an important role in tumor development and progression in different cancer types. FGFR genomic alterations, including FGFR gene fusions that originate by chromosomal rearrangements, represent a promising therapeutic target. Next-generation-sequencing (NGS) approaches have significantly improved the discovery of FGFR gene fusions and their detection in clinical samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 71 publications
0
108
0
1
Order By: Relevance
“…The high expressed levels of FGFR2 in colorectal [13], lung [14], gastric [15][16][17] cancer, coding mutations [18], and more recently, FGFR fusions that lead to pathway activation [19] have been demonstrated that the FGFR2 has a signi cant oncogenic potential across multiple cancer types. ROC analysis was employed to compare the predictive accuracy of the methylation status of patients with gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The high expressed levels of FGFR2 in colorectal [13], lung [14], gastric [15][16][17] cancer, coding mutations [18], and more recently, FGFR fusions that lead to pathway activation [19] have been demonstrated that the FGFR2 has a signi cant oncogenic potential across multiple cancer types. ROC analysis was employed to compare the predictive accuracy of the methylation status of patients with gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…However, several other commercially available NGS platforms have employed both DNA and RNA sequencing for evaluation of FGFR gene rearrangements and fusions. DNA-based methods are more stable than RNA, but detection of novel fusions are limited when compared to RNA-based methods, particularly when large intronic regions are involved [ 56 ]. Often, RNA fusion analysis identifies more alterations than DNA fusion analysis, whereas DNA sequencing did not detect any fusions RNA sequencing was unable to [ 57 ].…”
Section: Discussion and Future Considerationsmentioning
confidence: 99%
“…However, WGS has the advantage of identifying a large number of rearrangements and characterizing breakpoints, including those in non-coding regions, and it is particularly useful for the discovery of novel fusions. WES offers the ability to evaluate DNA contained in all exonic regions of the genome [ 56 ]. WTS via RNA next-generation sequencing has the ability to detect rare or novel fusion events better than targeted RNA sequencing or DNA-based methods; one such test is the Caris MI Transcriptomeℱ, which has received FDA Breakthrough Device designation for detection of novel FGFR biomarkers from FFPE tumor tissue [ 59 ].…”
Section: Discussion and Future Considerationsmentioning
confidence: 99%
“…It is possible to characterize exact breakpoints, including those in non-coding regions. However, WGS is expensive and time consuming due to its enormous data output and intensive analysis [7]. An alternative to WGS can be whole exome sequencing (WES).…”
Section: Comprehensive Technologies: From Wgs To Wtsmentioning
confidence: 99%
“…Currently there are different approaches available to detect fusions in a targeted setup: hybrid capture-based methods, amplicon-based methods and anchored multiplex PCR (see Figure 1). Various off-the-shelf panels are available for all approaches as summarized by De Luca et al and compared by Heydt et al [7,12]. Hybrid capture-based approaches have the advantage to cover larger areas including flanking regions of the target area.…”
Section: Dna Vs Rna-based Targeted Sequencingmentioning
confidence: 99%